Perbandingan Motivasi Belajar Bahasa Inggris Antara Siswa Kelas X-IPA dan Kelas X-IPS - Yulianti Hidayah; Fathul Zannah; Nana Citrawati Lestari (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
Often science (IPA) students tend to be considered smart and diligent in studying, but is the motivation of students majoring in science also higher than students majoring in social studies (IPS)? Based on the above thoughts, the researcher is interested in knowing how to compare the motivation to learn English between students in class X-IPA science and grade X-IPS social studies at SMAN 5 Banjarmasin. The purpose of this study was to determine the comparison of students' motivation to learn English between students in class X-IPA and class X social studies at SMAN 5 Banjarmasin. The comparison of motivation focuses on integrative motivation and instrumental motivation. The type of research used in this research is descriptive research. The data of this study were sourced from primary data collected through a google form questionnaire/questionnaire. The data analysis technique used is the descriptive percentage analysis method by calculating the frequency and percentage of answers to each item in the questionnaire. Based on the conclusion, it is known that the integrative learning motivation and the instrumental learning motivation of students in class X-IPA are lower than students in class X social studies.